PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK DAN KEMAMPUAN BERPIKIR KRITIS PADA KD 3.14 MATERI SISTEM PERTAHANAN TUBUH KELAS XI SMA - Julianti, Putri; Yustina, Yustina; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to produce student worksheets (LKPD) based scientific approach and thinking critical ability on the KD 3.14 subject body defense system grade XI High School. This development research was conducted at the Laboratory of Biological Education Department of PMIPA Faculty of Teacher Training and Education Universitas Riau and SMAN 14 Pekanbaru. This research was conducted from March to June 2018. The type of research used in this development research refers to the Research and Development (R & D) research approach using the ADDIE model consisting of five stages, namely analyze, design, development, implement and evaluate. This research is only done until development stage. The instrument used is validation sheet and questionnaire of respondent. Furthermore, limited trials were conducted to 13 students of Biology education and 25 students of class XI SMAN 14 Pekanbaru. Research data were analyzed using descriptive analysis. The results of LKPD validation are based on a scientific approach and critical thinking skills for the material of the body's defense system seen from 3 aspects: design aspects, pedagogic aspects, and content aspects. The value of LKPD validity is based on a scientific approach and critical thinking skills in the design aspect, with a score of 3.89 valid categories, the validity value of pedagogic aspects, with a score of 3.91 valid categories, while the validity value in the feasibility aspect is filled with a score of 3.95 valid categories. Student responses on all aspects are categorized both with score 4.19 and the response of learners on all aspects are categorized very well with score 4.32. The results of the answer analysis on trial II show the average value of 89 with very good category. LKPD based on a scientific approach to the material of the body's defense system can increase understanding and knowledge about the body's defense system and can improve students' critical thinking skills.Keywords: Development, LKPD, Scientific Approach, Critical Thinking, Body’s Defense System